Ataxia telangiectasia. Evaluation of radiosensitivity in cultured skin fibroblasts as a diagnostic test. Issue 5 (May 1978) - Cox, R; Hosking, G P; Wilson, J
Abstract : The sensitivity to x-ray inactivation of cultured skin fibroblasts from clinically confirmed and suspected cases of ataxia telangiectasia was compared with that of cultures from normal subjects. The results confirm previous observations of an association between ataxia telangiectasia and enhanced in vitro radiosensitivity, and also suggest that clonal survival of x-irradiated cultures of skin fibroblasts is a valuable technique for confirming the diagnosis of the disease.